(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2022)
As per ICH GCP, monitoring can be defined as “The act of overseeing the progress of a clinical trial, and of ensuring that it is conducted, recorded, and reported in accordance with the protocol, Standard Operating Procedures (SOPs), Good Clinical Practice (GCP), and the applicable regulatory requirement(s).” Clinical experiments are important for deeper understanding of how interventions work in humans. The aim of the monitoring of the clinical trial is to avoid errors that may compromise patient safety and results of the trial and enables more frequent monitoring of the integrity of the trial and could improve safety concerns by detecting errors earlier than expected. Risk-based monitoring in clinical trials is the process of identification, assessment, monitoring and mitigation of risks that could affect the quality or safety of a study. Centralized monitoring has a direct impact on the clinical trials. One of the most basic and fundamental need of centralized monitoring is to avoid the repetition in clinical trials, saving both time and Money. Central monitoring greatly influences the Patient safety, data integrity and monitoring costs in a clinical trial. This helps in increasing the effectiveness of the monitoring process reducing the burden on the sponsor. The basic and fundamental priority of a clinical trial is to ensure the safety and well-being of the subject. In this article, we will be focusing on how Centralized monitoring can increase the effectiveness and efficiency of the monitoring process and source data verification (SDV) in clinical trials with a special emphasis on Risk based monitoring (RBM).